2018
DOI: 10.1016/s0140-6736(18)31723-9
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin–clavulanate versus azithromycin for respiratory exacerbations in children with bronchiectasis (BEST-2): a multicentre, double-blind, non-inferiority, randomised controlled trial

Abstract: Australian National Health and Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 31 publications
4
72
0
1
Order By: Relevance
“…18 Exacerbations, including their resolution or failure to respond to the study medication, were predefined as per our previous study 19 and RCT. 11 The baseline state for each child was ascertained at enrolment with use of a validated cough diary card 18 and clinical examination. A nonsevere exacerbation was defined as an increase in cough frequency, a change in character of the cough (ie, from dry to wet, or an increase in sputum volume or purulence) for at least 3 consecutive days and without any accompanying dyspnoea, hypoxia (oxygen saturation <90% in air), or need for hospitalisation, according to the treating clinician.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…18 Exacerbations, including their resolution or failure to respond to the study medication, were predefined as per our previous study 19 and RCT. 11 The baseline state for each child was ascertained at enrolment with use of a validated cough diary card 18 and clinical examination. A nonsevere exacerbation was defined as an increase in cough frequency, a change in character of the cough (ie, from dry to wet, or an increase in sputum volume or purulence) for at least 3 consecutive days and without any accompanying dyspnoea, hypoxia (oxygen saturation <90% in air), or need for hospitalisation, according to the treating clinician.…”
Section: Methodsmentioning
confidence: 99%
“…A nonsevere exacerbation was defined as an increase in cough frequency, a change in character of the cough (ie, from dry to wet, or an increase in sputum volume or purulence) for at least 3 consecutive days and without any accompanying dyspnoea, hypoxia (oxygen saturation <90% in air), or need for hospitalisation, according to the treating clinician. 11 An exacerbation was considered resolved when a cough score had returned to baseline for at least 2 consecutive days after randomisation and commencement of study medications, and when any other new symptoms associated with the episode (such as fever, See Online for appendix lethargy, or general malaise) had resolved. An exacerbation was considered resolved even if the child exited the study protocol for any reason after resolution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BEST‐1, the first placebo‐controlled RCT for exacerbations, showed the efficacy of amoxicillin‐clavulanate and azithromycin over placebo (relative risk of bronchiectasis resolution by day 14 was 1.50 (95% CI: 1.08–2.09; P = 0.015) and 1.41 (95% CI: 1.01–1.97; P = 0.042), respectively) . BEST‐2 described that although azithromycin was non‐inferior (within a 20% margin) to amoxicillin‐clavulanate for resolving exacerbations in children with non‐severe bronchiectasis, children on azithromycin had a longer exacerbation duration and increased risk of inducing macrolide resistance . Data over the last decade have shown that bronchiectasis exacerbations can be successfully reduced by 40–50% (using long‐term oral azithromycin for 6–26 months in children and adults) by using inhaled fluoroquinolones (rate ratio = 0.74, 95% CI: 0.62–0.87) …”
Section: Disclosure Statementmentioning
confidence: 99%